Crecimiento de la masa muscular del miembro posterior del Ñandú Grande (Rhea americana) durante la vida postnatal - Picasso, Mariana Beatriz Julieta (2012)
The aim of this work is to characterize the growth of the hindlimb muscle mass of the Greater Rhea Rhea americana at different postnatal ages. Twentyone muscles were dissected and weighed in 22 specimens of various ages (ranging from a month to full adults) to evaluate their proportion in relation to the body mass and their contribution to the extension and flexion functions. The hindlimb muscles of the Greater Rhea accounted for a high percentage of the body weight during the postnatal growth period. Also, they were distinguished by a predominance of the extensor muscles, in particular those that extend the tibiotarsus-tarsometatarsus joint and the pelvis-femur joint, except in the digits where there was a predominance of the flexor muscles. These features seem to reflect, from an early age, the commitment of the hindlimb muscle system to a high-speed terrestrial locomotion.